Louis Armstrong loves Guy Lombardo! Acknowledging the smoother roots of jazz - Wald, Elijah (Jazz Research Journal, 2007)
Though Guy Lombardo and the Royal Canadians were always considered the sweetest of American dance bands and the antithesis of what is usually called jazz, Louis Armstrong regularly named them as his favorite orchestra. This judgment is usually dismissed as an odd quirk, but by exploring it we can learn something about what made Armstrong unique. Likewise, it is worth examining Armstrong’s admiration for classical virtuosos like Herbert Clarke of the Sousa band. In broader terms, we cannot understand the evolution of jazz if we do not explore the deep African-American classical tradition and the extent to which artists like Armstrong and Lombardo shared a single world, and appealed to a broadly overlapping audience. Sweet orchestras and classical concert music, rather than being the opposite of jazz, were among the many inspirations for Armstrong and his peers, and our understanding and appreciation of these musicians is increased when we realize the breadth of their interests.